2011
DOI: 10.1007/s10895-011-1027-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Luminescent Properties of M2V2O7: Eu (M=Sr, Ba) Nanophosphors

Abstract: A solution combustion route for the synthesis of Eu(3+)-activated M(2)V(2)O(7) (M = Sr, Ba) and their luminescent properties have been investigated. Structure and luminescent characteristics of Sr(2)V(2)O(7):Eu(3+) and Ba(2)V(2)O(7):Eu(3+) nanophosphors have been studied by x-ray diffraction, scanning electron microscopy, transmission electron microscopy, fluorescence spectrometry and Fourier transform infra-red spectroscopy. The incorporation of Eu(3+) activator in these nanoparticles has been checked by lumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Development of red-light-emitting phosphor that can be used as one of the primary components of white-light-emitting devices has been established to be an interesting goal of research for its versatile applications [1,2]. Rare earth-doped complex oxides such as vanadates, tungstates and molybdates have been proven to be ideal hosts for optical and photonic applications [3][4][5][6]. Such luminescent materials are extensively used as high-resolution optical devices such as cathode ray tubes (CRTs), electroluminescent and field emission display devices, plasma display panels (PDPs) and fluorescent lamps (FLs) or as nanophosphors for biological leveling [2,3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of red-light-emitting phosphor that can be used as one of the primary components of white-light-emitting devices has been established to be an interesting goal of research for its versatile applications [1,2]. Rare earth-doped complex oxides such as vanadates, tungstates and molybdates have been proven to be ideal hosts for optical and photonic applications [3][4][5][6]. Such luminescent materials are extensively used as high-resolution optical devices such as cathode ray tubes (CRTs), electroluminescent and field emission display devices, plasma display panels (PDPs) and fluorescent lamps (FLs) or as nanophosphors for biological leveling [2,3,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the bulk YVO 4 doped with RE 3? ions is more efficient than their nanocounterparts [7], as a decrease in particle size results in more surface dangling bonds that can easily absorb OH -and CO 3 2-from the surrounding environment such as aqueous medium and atmosphere during wet chemical synthesis route. In order to get a phosphor of high quantum efficiency, better luminescence, a good thermal and chemical stability various synthesis routes have been employed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The FE-SEM images show that the particle size is between 0.5-3. The particle size of the Sr 2.85 (VO 4 ) 2 :0.1Eu phosphors increases with the increasing of the annealing temperature and agglomeration decreased [70]. In fact, agglomeration of the as-synthesized powder after annealing at 1150°C almost vanished, producing bulk-like particles.…”
Section: Surface Morphology Of M 3-3x/2 (Vo 4 ) 2 :Xeu Phosphormentioning
confidence: 97%
“…The microstructure of the as-synthesized and annealed sample shows a porous microstructure due to rapid release of gases by-products during the combustion [56].…”
Section: Surface Morphology Of M 3-3x/2 (Vo 4 ) 2 :Xeu Phosphormentioning
confidence: 99%
“…Their red-emitting properties make them an attractive material with wide range of applications in electronic devices. [23] Zhi Zhou and colleagues synthesized Sr 2 V 2 O 7 :Eu 3+ phosphors using a solid-state reaction method and reported their luminescence properties. The charge compensate of the obtained phosphor was studied in detail.…”
Section: Introductionmentioning
confidence: 99%